A Study to Assess the Determinants Affecting the Health Seeking Behavior and their Effect on Utilization of Antenatal Services among the Pregnant Women: A Cross - Sectional Study - Wadhwa, Medha; Chatterjee, Subhasish; Gadhavi, Varsha (International Journal of Psychosocial Rehabilitation, 2020)
Introduction: Good maternal health is the foundation of a healthy society. The maternal health is influenced by the women’s own health-seeking behavior. The present study aims to highlight the factors affecting the maternal health-seeking behavior of pregnant women in Vadodara and the effect of these factors on the utilization of the antenatal care services at the health center. Material & Methods: The study is undertaken at five different PHCs of Vadodara district from each of the zones. The sample size of the study comprises 83 pregnant women who willingly gave consent to participate in the study and were in their second or third trimester. The data was gathered using the primary method of data collection through a schedule to assess the factors affecting the health-seeking behavior of pregnant women. The data was assessed on a five-point Likert scale and analyzed using SPSS version 21. Findings: There were 17 women showing positive health-seeking behavior, 40 showing moderate behavior, and 26 showing the negative health-seeking behavior related to institution and system determinants. There were 26 women showing positive health-seeking behavior, 38 showing moderate behavior, and 19 showing negative health-seeking behavior with respect to social and cultural determinants. There were 16 women showing positive health-seeking behavior, 20 showing moderate behavior, and 47 showing negative health-seeking behavior with respect to individual and household determinants. There is no difference in the health-seeking behavior of the pregnant women for all the determinants, as the p-value of the Kruskalwallis test is non-significant (p-value more than 0.05). Conclusion: The study highlights that the female may possess a negative health-seeking behavior with respect to her individual and household determinants, but a positive health-seeking behavior with respect to institutional and systemic or social and cultural beliefs may be a motivating factor in the utilization of the services at the health center in the prescribed manner. The study focuses that health-seeking behavior with respect to one determinant cannot be the deciding factor, but an aggregate of behavior influenced by an interaction of various determinants affects the utilization of the services.